2018
DOI: 10.1136/bmjpo-2018-000339
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the performance of blood glucose monitoring systems for monitoring dysglycaemia in neonatal patients

Abstract: ObjectiveTo validate a three-step protocol that assesses the clinical risk associated with using blood glucose monitoring systems (BGMS) in neonates for the management of dysglycaemia.MethodThe three-step validation approach included confirmation of the accuracy of the reference method using National Institute of Standards and Technology (NIST) glucose standards, assessment of analytical risk performed on whole blood collected from paediatric patients routinely tested for glucose and a clinical risk assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…There has also been recent evidence published that the POC BGM employed by our institution and used in this study (Accu-Chek® Inform II) showed analytical interference with ascorbic acid, lactose, galactose, N -acetylcysteine and glutathione in neonatal patients. 40 Further studies should be conducted with both this BGM and others to assess interference of ascorbic acid as well as other chemicals on blood glucose accuracy. Additionally, this study was a retrospective case series; thus, all data collected were highly dependent on the accuracy of documentation.…”
Section: Discussionmentioning
confidence: 99%
“…There has also been recent evidence published that the POC BGM employed by our institution and used in this study (Accu-Chek® Inform II) showed analytical interference with ascorbic acid, lactose, galactose, N -acetylcysteine and glutathione in neonatal patients. 40 Further studies should be conducted with both this BGM and others to assess interference of ascorbic acid as well as other chemicals on blood glucose accuracy. Additionally, this study was a retrospective case series; thus, all data collected were highly dependent on the accuracy of documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that better clinical outcomes are associated with improved glycemic control [16][17][18]. However, there is increasing concern about the accuracy and reliability of glucose meters [1,13,19]. A feasible method to assess the system accuracy of glucose meters is to compare the glucose measurement values obtained from the BGMS with the reference glucose values from the biochemical analyzer of the central laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…37 An extreme level of low blood glucose can cause several life-threatening conditions in neonates, such as apnea, irritability, lethargy, seizures, and even brain damage. 38 Failure to do bedside glucose monitoring as ordered can result in a dangerous situation to the neonates and hence, it is really important to increase the awareness of the consequences of omission 39 and to provide better bedside glucose monitoring devices 40,41 to reduce the morbidity caused by missed nursing care. Conversely, the top three least frequent missed nursing care could be related to the fact that they are too obvious to be missed and are routinely audited by the nursing units.…”
Section: Discussionmentioning
confidence: 99%